Assessment of cricket frass as a sustainable organic fertilizer: Effects on seedling establishment, growth and fruit yield of zucchini (Cucurbita pepo) - Clarcky Andrianorosoa Ony; Cédrique Lova Solofondranohatra; Tanjona Ramiadantsoa; Andrianjaka Ravelomanana; Tantely Maminiaina Razafimbelo; Andry Andriamananjara; Sakib Burza; Sabrina Simon; Mahardika Putra Purba; Brian L. Fisher (PLoS ONE, 2026)
Inherently poor soil quality, compounded by widespread soil degradation from unsustainable farming practices, continues to constrain agricultural productivity in Madagascar. As a result, fertilizer application has become essential for improving crop yields. This study assessed the effects of cricket frass fertilizer (CFF) from Gryllus madagascariensis on zucchini ( Cucurbita pepo ) production, in comparison with cattle manure (CM) and NPK, across two contrasting sites in southeastern Madagascar: Tsaratanàna, a relatively nutrient-rich coastal site, and Namohora, a nutrient-poor inland site. Seven fertilizer treatments were evaluated: an unfertilized control, CM (3.75 g N/plant), NPK (3.75 g N/plant), CFF at the baseline dose (3.75 g N/plant), ¼ × CFF (0.94 g N/plant), 2 × CFF (7.50 g N/plant), and a CM + CFF combination (7.50 g N/plant total). Plant survival was highest with ¼ × CFF in Tsaratanàna and with 2 × CFF in Namohora. Plant height and leaf number generally increased with increasing CFF dose at both sites. Yield responses were site-dependent: NPK produced the highest yield in Tsaratanàna, whereas 2 × CFF produced the highest yield in Namohora. Overall, CFF improved zucchini survival, growth, and yield relative to the unfertilized control. CFF performance relative to cattle manure varied across sites but generally remained comparable or superior, whereas its performance relative to NPK was not consistently superior across sites. These findings indicate that CFF is a promising organic fertilizer for zucchini, particularly under nutrient-poor conditions.